Noncontact evaluation of the conductivity of CuPc thin films by near-field microwave microprobe method - Lkhamsuren, Enkhtur; Ragchaa, Galbadrakh (Scientific transaction of the National University of Mongolia. Physics, 2022)
Abstract The conductivity of copper II phthalocyanine (CuPc) thin films with different crystal structures and morphologies was evaluated by using a near-field microwave microprobe (NFMM) technique in the frequency range of 4-4.5 GHz. CuPc thin films annealed at 200 °C and 350 °C showed the a- and yS-phase crystal structures, respectively. Crystal phase structure and morphology of CuPc thin films were characterized by optical absorption spectra measurement, X-ray diffraction, and scanning electron microscopy methods. Conductivity measurements of CuPc thin films were done in the temperatures range of25-160 °C.